IMPLEMENTATION OF FLOOD DIRECTIVE IN POLAND IN THE CONTEXT OF FLOODPLAIN DEVELOPMENT - Głosińska, Ewa (Quaestiones Geographicae, 2014)
The Flood Directive (FD) aims to establish a framework for the assessment and management of flood risks, aiming at the reduction of the adverse consequences for human health, the environment, cultural heritage and economic activity (FD, Art. 1). The implementation of Directive is a multi-stage process, with the defined deadlines for the completion of each stage. The main aim of the paper is to present the process of Flood Directive implementation in Poland, including the present state of works on the implementation of particular stages. The evaluation of the significance of Directive implementation in Poland will also be presented.